The Influence of User Experience in Digital Learning Applications on Students’ Motivation and Retention in Indonesian Higher Education Institutions - Setyawan, Rachmat (Universitas Sains dan Teknologi Komputer, 2024)
This study is grounded in the growing integration of digital learning applications in Indonesian higher education and the need to understand how user experience (UX) influences students’ academic sustainability. The research aims to examine the direct effect of UX on student retention and the mediating role of learning motivation in explaining this relationship. A mixed-method approach was employed, involving a quantitative survey of 250 active university students using Likert-scale questionnaires and in-depth interviews with 10 selected participants, with data analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that user experience has a significant positive effect on learning motivation and student retention, while motivation also serves as a meaningful mediator in strengthening the relationship between UX and retention. These results indicate that well-designed digital learning experiences not only enhance students’ engagement but also contribute to their long-term academic commitment. The study contributes to the development of digital education management theory by integrating technological experience and motivational mechanisms into a unified empirical model, and it offers practical implications for universities seeking to improve student retention through strategic enhancement of digital learning platforms.